PENGARUH GRATITUDE TERHADAP FOMO (Fear of Missing Out) PADA REMAJA PENGGUNA MEDIA SOSIAL TIKTOK DI KOTA WAINGAPU - Maria Agithya R.E Nggilimara; Wahyuni Kristinawati (Bajang Institute, 2025)
This research aimed to examine whether there is an influence of gratitude on FOMO (Fear of Missing Out) behavior among teenage TikTok users in Waingapu City. The research method used was quantitative correlational with an accidental sampling technique. The number of subjects in this study was 138 teenagers from Waingapu who actively use TikTok. Data collection was conducted using two psychological scales: the gratitude scale and the FOMO scale, both of which had been tested for validity and reliability. The correlational test was carried out using linear regression analysis with bootstrapping, and the correlation coefficient obtained was -0.344, p = 0.036. This indicates that when gratitude increases by one unit, FOMO tends to decrease by 0.344 units. The t-value = -117 suggests that this effect is fairly strong.